Major approaches to bucomaxillofacial bone regeneration and remodeling with the use of biomaterials: a systematic review - Sánchez, Carlos Alberto (2022)
Introduction: The number of dental implants in the world has increased, totaling more than one million procedures per year. The development of biomaterials has represented an important therapeutic tool in the correction of bone defects. The bone regeneration process is initiated by successive mitosis of mesenchymal and endothelial stem cells, as well as by activation of osteoblasts and vascular proliferation guided by platelet-derived growth factors (PDGF) and TGF-β. Objective: To present, through a systematic review, the main results involving bone formation and remodeling in the maxillofacial system using biomaterials, cells and molecules in the appropriate biological niche of human bone. Methods: The research was carried out from July 2021 to August 2021 and developed based on Scopus, PubMed, Science Direct, Scielo, and Google Scholar, following the Systematic Review-PRISMA rules. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results: A total of 225 articles were found. After the selection process, 95 articles were recruited for analysis, 44 articles were selected and 43 articles were used in this study to compose the textual part. The selected articles had moderate quality in their clinical trials. The bias risks found do not affect the reliability of the results. As main findings, it was found that the osteoinduction process is influenced by several factors, requiring the presence of inducers, which include β-glycerolphosphate, ascorbic acid and dexamethasone. Mesenchymal cells acquire the morphology and components of osteoblastic membranes and start to express alkaline phosphatase to deposit extracellular matrix rich in calcium and certain proteins, such as osteopontin and osteocalcin. Bone morphogenetic proteins function as growth factors with a specific role in the proliferation and differentiation of mesenchymal stem cells present in the lesion's niche. Platelet-rich fibrin (PRF) stimulates bone regeneration more efficiently. Studies have reported that the addition of PRF with bone graft is associated with positive clinical results and is a good method of manipulating the bone graft during insertion into the maxillary sinuses and it stimulates bone regeneration. Conclusion: Optimized bone regeneration is a matter of great research to accelerate the osseointegration process, leading to reduced waiting time before any subsequent procedure. The balance between the biomaterial, mesenchymal stem cells, fibrin formation and platelet activation are responsible for the process and performance of bone regeneration or formation.